Acute exposure to ultraviolet‐B radiation modulates sex steroid hormones and receptor expression in the skin and may contribute to the sex bias of melanoma in a fish model. (3rd February 2014) - Mitchell, David L.; Fernandez, André A.; Garcia, Rachel; Paniker, Lakshmi; Lin, Kevin; Hanninen, Amanda; Zigelsky, Kyle; May, Matthew; Nuttall, Mark; Lo, Herng‐Hsiang; Person, Maria D.; Earley, Ryan
Summary Using the Xiphophorus fish melanoma model, we show a strong male bias for sunlight‐induced malignant melanoma, consistent with that seen in the human population. To examine underlying factors, we exposed adult X. couchianus fish to a single, sublethal dose of UVB and measured circulating sex steroid hormones and expression of associated hormone receptor genes over a 24‐h period. We found that a single exposure had profound effects on circulating levels of steroid hormones with significant decreases for all free sex steroids at 6 and 24 h and increases in conjugated 2‐estradiol and 11‐ketotestosterone at 6 and 24 h, respectively. Whereas ARα expression increased in male and female skin, neither ARβ nor either of the ERs showed significant responses to UVB in either sex. The rapid response of male androgens and their receptors in the skin after UVB irradiation implicates hormones in the male bias of skin cancer and suggests that the photoendocrine response immediately after UV exposure may be relevant to melanomagenesis.